A Nicotinamide Phosphoribosyltransferase Inhibitor, FK866, Suppresses the Growth of Anaplastic Meningiomas and Inhibits Immune Checkpoint Expression by Regulating STAT1 - Deng, Yuxuan; Hu, Boyi; Miao, Yazhou; Wang, Jing; Zhang, Shaodong; Wan, Hong; Wu, Zhen; Lv, Yifan; Feng, Jie; Ji, Nan; Park, Deric; Hao, Shuyu (Frontiers in Oncology, 2022)
Anaplastic meningioma is classified as a World Health Organization (WHO) grade III tumor and shows a strong tendency to recur. Although the incidence of anaplastic meningioma is low, the high rate of recurrence and death still makes treatment a challenge. However, targeting NAMPT to treat anaplastic meningiomas has not been reported. A proteomics analysis was performed to investigate the differentially expressed proteins between anaplastic meningiomas and fibrous meningiomas by micro-LC-MS/MS. The key metabolic enzyme nicotinamide phosphoribosyltransferase (NAMPT) showed upregulated expression in anaplastic meningiomas. In vitro, NAMPT inhibitor -FK866 reduced the viability of anaplastic meningiomas by inducing cell cycle arrest at the G2/M phase. Intriguingly, the NAMPT inhibitor -FK866 decreased the protein expression of immune checkpoints PD-L1 and B7-H3 by down-regulating the STAT1 and p-STAT1 expression in vitro. Furthermore, FK866 suppressed the growth of anaplastic meningiomas in an in vivo xenograft model. The expression of Ki-67 and immune checkpoint proteins (PD-L1 and B7-H3) showed significant differences between the group treated with FK866 and the control group treated with DMSO. In conclusion, the expression of NAMPT, which plays a crucial role in energy metabolism, was upregulated in anaplastic meningiomas. The NAMPT inhibitor -FK866 significantly suppressed the growth of anaplastic meningiomas in vitro and in vivo. More strikingly, FK866 potently inhibited immune checkpoint protein (PD-L1 and B7-H3) expression by regulating STAT1 in vitro and in vivo. Our results demonstrated that NAMPT inhibitors could potentially be an effective treatment method for patients suffering from anaplastic meningiomas.